(untitled) (Research, Society and Development, 2021)
This research aimed to evaluate the technological potential of genipap flour (Genipa americana L.) in freeze drying and oven drying processes. The ripened genipap fruits were harvested and submitted to pulp extraction, which after dehydration in an oven and freeze drying, were crushed to obtain the flours. When analyzed by X-ray diffraction, the flours were amorphous, with indicative of starch. In addition, the presence of water, aromatics and primary alcohols was observed by infrared spectra (FTIR). In micrograph (SEM) FPJDE was less porous and starches were identified. For thermogravimetry (TGA) similar thermal events occurred, it was important to verify the thermal behavior, humidity and ash present in the food. In the mineral composition, potassium, magnesium, manganese, iron, phosphorus, copper, and calcium were present, the flours as a source of manganese and with a high content of iron, potassium, copper and magnesium. It was concluded that the flours present a quantity of nutrients and favorable technological characteristics such as: thermal stability, humidity below that established by law for the manufacture and production of food.